UJI EFIKASI BEBERAPA ISOLAT BAKTERI ENTOMOPATOGEN TERHADAP KECOA (Orthoptera) Periplaneta americana (L.) DAN Blatella germanica (L.) DALAM SKALA LABORATORIUM - Monaliza Sekar Rini; Rully Rahadian; mochamad Hadi; Deni Zulfiana (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Cockroaches are the insect vectors of disease that can cause adverse effects on human health. Control cockroaches excessive use of insecticides can lead to residues in the environment and resistance cockroach. Therefore it is necessary to control the use of alternatives such as by biological agents such as entomopathogenic bacteria. This research used two isolates of entomopathogenic bacteria isolated from Spodoptera litura were found dead, Bacillus thuringiensis IPBCC collection and sterile distilled water as a control. Tests conducted by the spray and bait method at a concentration of 108. The results showed that all isolates entomopathogenic bacteria used in this research can cause mortality of cockroaches. Morphological observation and Koch's postulates test showed that the mortality of cockroaches likely caused by bacterial isolates were granted. SP4 bacterial isolates using spray method provides the highest mortality was 26.67% of the P. americana and 80% against B. germanica. Isolates of B. thuringiensis using bait influence the highest mortality of 10% of the P. americana and 6.67% against B. germanica. LT-50 was the most effective method of treatment of bacterial isolates SP4 spray against B. germanica was 2 hours 30 minutes 46 seconds.Keywords: Biological control, entomopathogenic bacterial, efficacy test